Clinical diagnosis of malignant pleural mesothelioma - Bianco, Andrea (J Thorac Dis, 2018)
Malignant pleural mesothelioma (MPM) is a tumour which, despite progress in diagnostic procedures and biomolecular research, has poor prognosis. Symptoms reflect extension of disease and include shortness of breath and chest pain. Unexplained pleural effusion and pleural pain in patients exposed to asbestos should raise the suspicion of MPM. MPM diagnosis requires imaging procedures X-ray and computed tomography (CT) scans; magnetic resonance imaging (MRI) better defines the extension of the tumor while PET scanning provides additional information on metabolic activity, metastases, and response to treatment. Thoracoscopic biopsy remains the most appropriate procedure for definitive diagnosis of mesothelioma. Multimodality treatment including surgery, chemotherapy and radiotherapy has been associated with a better survival in selected patients. Clinical translational research including new approaches targeting immune-checkpoints is opening new horizons which may lead to personalised treatments.